Constraints and Possibilities of Good Governance in South Asia - Ahmad, Peerzada Tufail; Wani, Hilal Ahmad (EDUCARE, 2013)
ABSTRACT: Accountability, transparency, and participation are the central themes of good governance. Good governance can mean different things to different countries. Since each country or region has a different context of governance,which it faces unique governance challenges. Therefore, it is important that the concept of âgood governanceâ is understood in the context of each country and region to find indigenous and pragmatic solutions to problems of governance. The application of the concept of good governance to developing countries that are at different development stages have unintended and serious consequences for the citizens, especially for poor. The issue of transferability of the notion of good governance to developing countries is not being adequately attended to, while formulating a reform agenda mostly backed by international donors, especially in the case of heavily indebted countries. Developing countries are being asked to do everything which works in developed countries and, consequently, the good governance agenda in the developing world has grown long over the years. South Asia is a region rich in culture and tradition and poor in governance and human development. This paper is an attempt to examine the possibility of South Asian model(s) of governance to capture and address the complexities and challenges of governance in this particular region.KEY WORDS: Good governance, constraints and possibilities, democracy and prosperity, and South Asian countries.Â Â About the Authors: Peerzada Tufail Ahmad, M.Phil. is a Ph.D. Student at the Department of International Relations KU (Kirikkale University) in Turkey; and Dr. Hilal Ahmad Wani is a Post Doctoral Fellow at the Centre for Peace and Strategic Studies UOI (University of Ilorin) in Nigeria. They can be contacted via e-mail at: pztufail.kat@gmail.com and wanihilal@gmail.comHow to cite this article? Ahmad, Peerzada Tufail & Hilal Ahmad Wani. (2013). âConstraints and Possibilities of Good Governance in South Asiaâ in EDUCARE: International Journal for Educational Studies, Vol.5(2) February, pp.147-160. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (December 22, 2012); Revised (January 23, 2013); and Published (February 17, 2013).Â  Â